The Shaping of Two Distinct Dendritic Spikes by A-Type Voltage-Gated K+ Channels - Yang, Sungchil; Tang, Cha-Min; Yang, Sunggu (Frontiers in Cellular Neuroscience, 2015)
Dendritic ion channels have been a subject of intense research in neuroscience because active ion channels in dendrites shape input signals. Ca2+-permeable channels including NMDA receptors (NMDARs) have been implicated in supralinear dendritic integration, and the IA conductance in sublinear integration. Despite their essential roles in dendritic integration, it has remained uncertain whether these conductances coordinate with, or counteract, each other in the process of dendritic integration. To address this question, experiments were designed in hippocampal CA1 neurons with a recent 3D digital holography system that has shown excellent performance for spatial photoactivation. The results demonstrated a role of IA as a key contributor to two distinct dendritic spikes, low- and high-threshold Ca2+ spikes, through a preferential action of IA on Ca2+-permeable channel-mediated currents, over fast AMPAR-mediated currents. It is likely that the rapid kinetics of IA provides feed-forward inhibition to counteract the delayed Ca2+ channel-mediated dendritic excitability. This research reveals one dynamic ionic mechanism of dendritic integration, and may contribute to a new understanding of neuronal hyperexcitability embedded in several neural diseases such as epilepsy, fragile X syndrome and Alzheimer's disease.